An assessment of some methods of storage of rubber seeds and undefatted seed cake - Otoide V O; Begho E R
Rubber seeds( fresh and predried whole seeds and kernels) were stored by four methods, viz: in polythene bags, plastic jerry cans, nylon-matted bags and on the floor. After a period of two months of storage, the fresh seeds recorded significantly higher levels of mouldiness compared to the pre-dried seeds. While 10-100;of the fresh whole seeds and kernels were mouldy, depending on the storage method, 6.7-30;of the pre-dried whole seeds and kernels were mouldy. The moisture contents of the fresh seeds dropped significantly from 29.7;to less than 10;except for those stored in plastic jerry cans and fresh whole seeds in polythene bags. A trace of mouldiness was observed on the surface of the undefatted seed cake stored in nylon-matted bags. In all cases, mouldiness was caused by Aspergillus sp. A few insects (Tribolium sp.) were observed in the fresh kernels stored on the floor and in nylon-matted bags. From the preliminary results obtained it is concluded that drying rubber seeds before storage is desirable to minimise mouldiness.
Keywords: Rubber seed cake; Rubber seed kernel; Seed storage